Representasi Perempuan Jawa Dalam Film Drama Biografi Sejarah Bumi Manusia - Andriani, Aisyah (Journal Communication Specialist, 2025)
This study discusses the depiction of Javanese women in the Indonesian historicalbiographical drama film "Bumi Humans", especially in the role of mistress who is identical to Javanese women. Sha Ine Febryanti who received an award at the Indonesian Movie Actors (IMA) Awards in 2016 as the Best Female Actor. Exploitation of a woman's body began to be highlighted and used as a commodity, aka a seller. Women in films are placed as a tool to attract men's attention. The representation of women in Indonesian historical biographical drama films cannot be separated from the role of mistresses who are synonymous with women. The method used by researchers in this thesis research is Sara Mills's discourse analysis method. This method focuses attention on the discourse of feminism. How women are shown in the text, both in novels, pictures, photographs and news. In addition, Mills also pays more attention to the position of the subject-object and the position of the reader. The research methodology used is a critical paradigm with a qualitative approach. The data used in this study is a series of dialogues and images (scenes) in the film Bumi Manusia. The results of this study are that women who stand alone as feminism are depicted by the main character as an indigenous concubine. Women actually cannot equal the position of men in the highest positions. Because women still have a domestic life such as wanting to have children and other household life according to the opinion of feminists that women do not have rational thoughts. Keywords: Subject, Object, Reader, Feminism, Women, Human Earth.